The education of the Hispanic education, selected essays - Gastic, Billie; Verdugo, Richard R.; Berardino, Michael; Coronado, Diana Yadira Salas (Hispanic population in the United States (Charlotte, N.C.), 2013)
This volume brings together the latest research and scholarship on Latinos in the United States. This book is special in terms of the broad scope of topics covered and methodologies employed in pursuit of knowledge about Latino students. This collection is also unique in that it features the work of more than a dozen Latino scholars--both early-careerand established--applying their research expertise to investigate and elucidate the educational experiences of Latinos in the United States.The themes that are discussed in the chapters of The Education of the Hispanic Population: Selected Essays, reflect the wide-ranging discussions that are occurring in schools and school districts across the country and issues that are being carefully investigated by researchers who are committed to contributing thoughtful and meaningful scholarship of consequence for improving conditions for Latino youth.